Chapter 26 Addiction treatment providers' engagements with the Brain Disease Model of Addiction - Barnett, Anthony (Taylor & Francis, 2022)
Debates about the etiology of addiction have a long history and continue to the present day. In contemporary societies, the brain disease model of addiction (BDMA) continues to receive strong support, in particular, from US agencies such as the National Institute on Drug Abuse (NIDA) and the American Society of Addiction Medicine. Today, there continues to be a significant investment in addiction neuroscience research globally. However, the views of addiction treatment providers about the BDMA, and its clinical impact, are often ignored when debates led by public health researchers and neuroscientists dominate discourse about the neurobiology of addiction. In this chapter, we start by providing a brief history of the biomedicalization of addiction. Moving beyond the question of 'Is addiction a brain disease, or not?', we summarize providers' views about the BDMA and its impact on clinical practice. Drawing on recent critical drug studies scholarship, we critique how a simplistic, linear 'bench to bedside' model of addiction neuroscience translation elides the role treatment providers play in translating neuroscience. Finally, we consider the effects of how the enactment of addiction as a brain disease within policy impacts treatment, and how addiction might be enacted in other ways in future policy frameworks.